2022
DOI: 10.1002/jhm.12911
|View full text |Cite
|
Sign up to set email alerts
|

Current use, training, and barriers in point‐of‐care ultrasound in hospital medicine: A national survey of VA hospitals

Abstract: Background: Point-of-care ultrasound (POCUS) can reduce procedural complications and improve the diagnostic accuracy of hospitalists. Currently, it is unknown how many practicing hospitalists use POCUS, which applications are used most often, and what barriers to POCUS use exist. Objective: This study aimed to characterize current POCUS use, training needs, and barriers to use among hospital medicine groups (HMGs). Design, Setting, and Participants: A prospective observational study of all Veterans Affairs (VA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Lack of ultrasonography, a lack of organized curriculum, a lack of a national standard, and a lack of training were the top barriers to US usage raised by residents. Lack of ultrasound equipment used to be a signifcant issue when POCUS frst began in the West, but lack of training was also a signifcant issue in other nations [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Lack of ultrasonography, a lack of organized curriculum, a lack of a national standard, and a lack of training were the top barriers to US usage raised by residents. Lack of ultrasound equipment used to be a signifcant issue when POCUS frst began in the West, but lack of training was also a signifcant issue in other nations [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…As POCUS usage continues to expand, 7,19 AI-enabled devices represent a possible means to enhance competency among novice users and aid in interpretation. 13,14,20 In this randomized, controlled trial, we observed that internal medicine residents randomized to carry an AI-POCUS device for two weeks without feedback were able to obtain A4C views more quickly, had higher A4C image quality scores, and were more likely to identify reduced systolic function compared to residents who carried non-AI devices.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] In response to the growing evidence supporting the use of POCUS for patient care, medical schools, residency programs, and professional societies have developed training programs for its safe and effective usage. [5][6][7] In addition, several organizations have established guidelines in an effort to standardize POCUS training. 3,8 Barriers to implementing more universal training measures include time constraints within training programs, a paucity of faculty credentialed for supervision, limiting funding, the need for established quality assurance protocols, and a lack of standardized assessments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…New training needs are regularly identified in the modern clinical environment, and faculty workforce development remains challenging. Within the sphere of hospital medicine some recent calls include health and healthcare equity improvement, 14 addiction medicine, 15 and point‐of‐care ultrasound 16 . As experts respond to these needs and train‐the‐trainer models are designed, we recommend they consider the following based on our experience: …”
Section: Lessons For Other Emerging Educational Areasmentioning
confidence: 99%